Patriotism Explored in Whitman's "O Captain! My Captain!" - Walfajri, Annisa (Linguistika Kultura, 2023)
Exploring patriotism in Walt Whitman's "O Captain! My Captain!" delves into leadership, sacrifice, and emotional dynamics amid Civil War sentiment. Focusing on the symbolism of the Captain and the ship, this article examines the intricate relationship between patriotism and mourning. The Captain symbolizes a guide through challenge and sacrifice, while the ship represents the nation's collective journey. Celebratory yet sorrowful, the poem uses metaphor and repetition, portraying Lincoln as the Captain and America as the ship. The study concludes by underscoring the poem's timeless reflections on patriotism, leadership, sacrifice, and unity. In essence, it unveils layers of meaning within the Captain's persona. It highlights the poignant connection between individual and national fate during a tumultuous period.